2011
DOI: 10.1080/09593330.2010.543930
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of production of extracellular polymeric substances byArthrobacter viscosusand their interaction with a 13X zeolite for the biosorption of Cr(VI)

Abstract: In this work we aimed to optimize the production of extracellular polymeric substances (EPS) by an Arthrobacter viscosus biofilm supported on 13X zeolite to be used in the biosorption of Cr(VI). The optimization parameters were agitation rate, work volume, pH and glucose concentration. Following the optimization of EPS production, the biofilm was used in the biosorption of hexavalent Cr from liquid solutions. Differences between the use of dead or active biomass and between the performance of zeolite in powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…The vital role of EPS along with the cell in the adsorption and reduction of chromium has been noted recently (Ozturk et al 2009;Sheng et al 2010;Quintelas et al 2011). A detailed study on bio-removal of chromium by indigenous bacterial isolates from tannery polluted places has also been reported (Sundar et al 2011).…”
Section: Introductionmentioning
confidence: 89%
“…The vital role of EPS along with the cell in the adsorption and reduction of chromium has been noted recently (Ozturk et al 2009;Sheng et al 2010;Quintelas et al 2011). A detailed study on bio-removal of chromium by indigenous bacterial isolates from tannery polluted places has also been reported (Sundar et al 2011).…”
Section: Introductionmentioning
confidence: 89%
“…The concept of combining bacterial capacity for biosorption of heavy metals with a zeolitic support was originally proposed by Neves and Tavares. The Arthrobacter viscosus bacterium supported on zeolites was extensively used for the treatment of Cr(VI) solutions, and several zeolites were succesfully employed as support (natural clinoptilolite or synthetic FAU, MFI, MOR and BEA zeolites) [24,40,[136][137][138][139][140][141][142][143]. This bacterium is able to form a biofilm on the zeolitic surface, as reported by Lameiras et al The authors found that the removal percentages obtained for the biofilm-laden zeolite sorbent are similar than those previously obtained using instead granular activated carbon (GAC) as support [144].…”
Section: Zeolites As Supports For Bioremediation Of Cr and As Oxyanionsmentioning
confidence: 99%
“…LB medium favors the growth of P. putida in batch, but probably it does not allow the production of exopolysaccharides molecules (EPS) on the vermiculite particles, which are crucial substances contributing to bind significant amounts of heavy metals (Pal and Paul 2008;Gadd 2009). Many authors, in fact, confirm that EPS production by several bacteria species normally increase according to their nutrients starvation and environmental stress conditions (Sutherland 2001;González et al 2010;Fang et al 2011;Quintelas et al 2011). …”
Section: Batch Assays For Water Remediationmentioning
confidence: 99%
“…Natural clays (e.g., vermiculite) have been studied as suitable low-cost materials to be used for wastewater treatment or as permeable barrier in landfills to avoid pollutants release Quintelas et al 2011;Malamis and Katsou 2013). The tetra-and octahedral structure of phyllosilicates, in fact, favors a high surface area and a high availability of negative charges.…”
Section: Introductionmentioning
confidence: 99%